2023
DOI: 10.1002/adfm.202213260
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Decay of Li‐Rich Layered Oxides: Mechanism, Modification Strategies, and Perspectives

Abstract: Li-rich layered oxides (LLOs) have been considered as the most promising cathode materials for achieving high energy density Li-ion batteries. However, they suffer from continuous voltage decay during cycling, which seriously shortens the lifespan of the battery in practical applications. This review comprehensively elaborates and summarizes the state-of-the-art of the research in this field. It is started from the proposed mechanism of voltage decay that refers to the phase transition, microscopic defects, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 285 publications
(197 reference statements)
0
11
0
Order By: Relevance
“…Voltage decay is also a primary factor that affects battery performance. It will result in a continuous reduction of energy density and increase the difficulty of practical application. , Therefore, comprehending the underlying mechanism and identifying effective solutions at the atomic level are imperative for overcoming this bottleneck. The galvanostatic charge–discharge curves of the Li- and Mn-rich (LMR) cathode exhibit a high discharge capacity but rapid voltage fade and capacity loss concurrently during cycling (Figure f) .…”
Section: Atomic Manufacturing For Electrochemical Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Voltage decay is also a primary factor that affects battery performance. It will result in a continuous reduction of energy density and increase the difficulty of practical application. , Therefore, comprehending the underlying mechanism and identifying effective solutions at the atomic level are imperative for overcoming this bottleneck. The galvanostatic charge–discharge curves of the Li- and Mn-rich (LMR) cathode exhibit a high discharge capacity but rapid voltage fade and capacity loss concurrently during cycling (Figure f) .…”
Section: Atomic Manufacturing For Electrochemical Performancementioning
confidence: 99%
“…Benefiting from the reduced voltage hysteresis and polarization, it exhibits higher potential and energy density . The metal-doping strategy at the atomic level decreases the intrinsic antisite defect concentration, eliminating the voltage hysteresis and improving the initial Coulombic efficiency . Therefore, the problem of voltage hysteresis can be effectively solved by adjusting the intrinsic crystal structure of materials through atomic manufacturing.…”
Section: Atomic Manufacturing For Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the AR-based voltages reported in experimental studies. 9–12,27 Additionally, Fig. S3,† which represents the net charge variation of anions upon the charge/discharge process, indicated that the four material systems are governed by the AR mechanism, but the presence of (non-)hysteretic anion activity is also suggested.…”
mentioning
confidence: 99%
“…3–6 This degradation occurs because Mn 4+ at the octahedral site, which is coordinated with six oxygen ions, initiates oxygen oxidation, resulting in destabilisation of the crystal framework upon charging, because cationic oxidation for further oxidation to Mn 5+ during delithiation is complicated owing to crystal field theory energetics. 7–9 Based on this understanding, a similar model of monoclinic Li 2 TiS 3 , which is recognised as a redox-inactive cathode, was investigated and successfully synthesised to fully exploit the high theoretical capacity (∼339 mA h g −1 ) 9–13 and integrate it as a promising cathode with S-based solid electrolytes. 14–17 Consistent with Li 2 MnO 3 , the chemical state of the Ti ions in the Ti-based Li-rich sulphide was Ti 4+ , and its activity was unfeasible because no redox-capable 3d electrons exist in the valence band.…”
mentioning
confidence: 99%